Eficiencia de la bioaumentación y bioestimulación en la biodegradación de petróleo por bacterias nativas, provincia de Talara, región Piura - Baca Llontop, Katty Yesenia (2019)
ABSTRACT The objective of the research was to determine the efficiency of bioaugmentation and biostimulation in the biodegradation of petroleum by bacteria native to the province of Talara, Piura region. In the descriptive phase, the time of use of the petroleum and the number of emulsifying activity units (EAU) of five cultures of hydrocarbonoclastic bacteria were quantified. In the explanatory phase, the chemical, microbiological and toxicity characteristics of the experimental soil were determined, as well as the efficiency of the bioaugmentation and biostimulation in the petroleum biodegradation. It was determined that the hydrocarbonoclastic bacteria used the oil in a time of 60 and 80 hours, and the quantification of EAU was in a range of 0,716 – 1,569 EAU mL-1. The experimental soil presented a total hydrocarbon content (38899 mg kg-1), total microorganisms (2,4x106 NMP g-1) and hydrocarbonoclastic microorganisms (1,5x105 NMP g-1) and severe toxicity level according to the germination index of the radish. The maximum population of total microorganisms and hydrocarbonoclastic was reached at 60 and 90 days, respectively. Germination rates increased and toxicity levels decreased. With the bioaugmentation mixed consortium bioassay + biostimulation treatment, a low level of toxicity was reached at 90 days and 78% efficiency in petroleum biodegradation. The efficiency of the biodegradation of oil by bioaugmentation was demonstrated with a mixed consortium plus biostimulation.